Effectiveness of Implementing Traditional Games on Basic Motor Skills in Students of Phase A at SDN 2 Buluagung - Muhammad Soleh Fudin; Nur Ahmad Rifa’i; Nendra Febrianto; Sugeng Sulendro; Dilshodbek Mamajonov (CV Media Inti Teknologi, 2025)
This study aims to analyze the effect of implementing traditional games on the basic motor skills of phase A students at SDN 2 Buluagung, Karangan District, Trenggalek Regency. This study was motivated by the importance of learning Physical Education, Sports, and Health (PJOK) in improving motor skills, physical fitness, and character of students through physical activities. The results showed that the basic motor skills of phase A students increased significantly after the implementation of traditional games. In the pre-test, 17 students were in the very low category with the smallest motor quotient score of 46 and the largest 67. In the post-test, basic motor skills increased with 12 students in the average category, 4 in the above average category, and 1 in the below average category, with the smallest motor quotient score of 79 and the largest 106. The normality test showed that the data was not normally distributed, so the analysis was carried out using a non-parametric test. The results of the Wilcoxon Signed Rank Test showed an increase in the basic motor skills of students after being given treatment. After being calculated using the N-Gain formula, the effectiveness of the implementation of traditional games reached a score of 90.76%, with a minimum value of 61.11 and a maximum value of 114.29. This study concludes that the implementation of traditional games has an effect and is effective in improving the basic motor skills of phase A students at SDN 2 Buluagung. In addition, this study contributes to the preservation of traditional games and offers an alternative method of learning PJOK that is interesting and effective.